Performance of tropical vertical subsurface flow constructed wetlands for leachate treatment at different hydraulic loading rates - Meetiyagoda, T.A.O.K.; Bandara, N.J.G.J.; Jinadasa, K.B.S.N.; Kalpage, C.S.; Pathirana, C.D.K. (2017 University of Sri Jayewardenepura, 2017)
This study is focused on the investigation of three different types of plant species namely; Narrow leaf Cattail (Typha angustifolia), Green Bulrush (Scirpus atrovirens) and Umbrella Palm (Cyperus alternifolius) for treatment of leachate. Twelve laboratory scale subsurface flow constructed wetland models were operated in batch mode. Four models, each containing similar plant species were fed with synthetic leachate having four different concentrations (25%, 50%, 75% and 100%) and 7 days HRT was given. The duration of a batch run was 12 weeks. Removal efficiencies of BOD5, COD, PO43-, TC, and TN were measured. Evapotranspiration (ET) loss of each test run was also assessed. According to the results, the constructed wetland planted with Umbrella palm and fed with 25% leachate showed the best pollutant removal efficiencies of 99.26% for BOD5, 99.61% for COD, 98.78% for TN and 97.34%for TC. Highest ET potential of 93.57% was also observed from the constructed wetland with umbrella palm fed with 25% leachate. Two way ANOVA analysis was carried out for each plant species and leachate concentration and the Umbrella Palm species was identified as the best for leachate treatment.
Keywords: Constructed wetlands, landfill leachate, plant species, pollutant removal